"A disorder which occurs on standing": The Earliest Account of Orthostatic Tremor by Pazzaglia. Issue 1 (24th February 2015) - Erro, Roberto; Antelmi, Elena; Bhatia, Kailash P.
Abstract: The earliest account of orthostatic tremor (OT) dates back to 1970, when Pazzaglia and colleagues reported on three patients with a peculiar disorder only occurring on standing. Although Pazzaglia et al. did not use the term OT, they first provided both the clinical and neurophysiological features of such a condition.